(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Climate change leads to changes in rainfall and extreme event. This phenomenon has already begun to transform the rainfall patterns in Malaysia. It was clearly proven when the northern and eastern states of Peninsular Malaysia such as Kelantan, Terengganu, Pahang, Perak and Johor were hit by the catastrophic floods in December 2014, events that have been described as the worst in decades. Although there are a number of studies in climate change and extreme rainfall events in Malaysia, there are still large knowledge gaps about their relationship. Understanding the shifts and predicting changing trends in rainfall distribution is needed for predicting and managing the floods.Â In this paper, Mann Kendall (MK) test and Sen's Slope estimator are employed to determine the trend of extreme rainfall events of various storm durations in the Pahang and Kelantan river basins. The results indicate that annual maximum daily rainfall for Pahang River basin and Kelantan River basin increased throughout 45 years. Results show that the percentage of stations with statistically significant trend (at 0.05 significance level) in the Kelantan River basin are higher compared to the Pahang River basin. Percentage of stations showing increasing trends were much higher for short duration rainfall (10, 30 and 60 minutes and Â 3 hours) compared to long duration rainfall (6, 12, 24, 48, 120 and 240 hours). This study will be useful for planning, designing and managing floods and stormwater systems in this area